Scaling the laws of thermal imaging–based whale detection - Zitterbart, Daniel P.; Smith, Heather R.; Flau, Michael; Richter, Sebastian; Burkhardt, Elke; Beland, Joe; Bennett, Louise; Cammareri, Alejandro; Davis, Andrew; Holst, Meike; Lanfredi, Caterina; Michel, Hanna; et al. (Journal of Atmospheric and Oceanic Technology, 2020)
Marine mammals are under growing pressure as anthropogenic use of the ocean increases. Ship strikes of large whales and loud underwater sound sources including air guns for marine geophysical prospecting and naval midfrequency sonar are criticized for their possible negative effects on marine mammals. Competent authorities regularly require the implementation of mitigation measures, including vessel speed reductions or shutdown of acoustic sources if marine mammals are sighted in sensitive areas or in predefined exclusion zones around a vessel. To ensure successful mitigation, reliable at-sea detection of animals is crucial. To date, ship-based marine mammal observers are the most commonly implemented detection method; however, thermal (IR) imaging–based automatic detection systems have been used in recent years. This study evaluates thermal imaging–based automatic whale detection technology for its use across different oceans. The performance of this technology is characterized with respect to environmental conditions, and an automatic detection algorithm for whale blows is presented. The technology can detect whales in polar, temperate, and subtropical ocean regimes over distances of up to several kilometers and outperforms marine mammal observers in the number of whales detected. These results show that thermal imaging technology can be used to assist in providing protection for marine mammals against ship strike and acoustic impact across the world’s oceans.
CRIS-Team Scopus Importer:2020-06-05